2022
DOI: 10.1021/acs.jnatprod.2c00888
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Polyprenylated Acylphloroglucinols Bearing a Lavandulyl-Derived Substituent from Garcinia xanthochymus Fruits

Abstract: Many type B polycyclic polyprenylated acylphloroglucinols (PPAPs) bear a lavandulyl-derived substituent, and the configurational assignment of this side chain can be difficult and sometimes leads to erroneous conclusions. In this study, 21 PPAPs, including the new xanthochymusones A–I (1–9), have been isolated from the fruits of Garcinia xanthochymus and structurally characterized. The relative configuration of the C-30 stereocenter was assigned by a combination of chemical transformations, 1H–1H coupling cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We have had a long-standing interest in confirming or correcting proposed structures of natural PPAPs and have corrected the structures of dozens of them, ,, so we decided to reinvestigate the assigned structures of UF, UG, AE, AF, UK, UO, and SA–SD. First, we reisolated furan-fused PPAPs UG, AE, and AF from Hypericum patulum .…”
Section: Resultsmentioning
confidence: 99%
“…We have had a long-standing interest in confirming or correcting proposed structures of natural PPAPs and have corrected the structures of dozens of them, ,, so we decided to reinvestigate the assigned structures of UF, UG, AE, AF, UK, UO, and SA–SD. First, we reisolated furan-fused PPAPs UG, AE, and AF from Hypericum patulum .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the polyprenylated benzophenones (belonging to PPAPs) isolated from G. xanthochymus fruits displayed potent cytotoxicity in different human cancer cell types [ 32 , 33 , 34 ]. Recently, 9 new and 12 known PPAPs were isolated from G. xanthochymus fruits, and 4 PPAPs showed moderate inhibitory activities against 3 hepatocellular carcinoma cell lines with IC 50 values in the range of 3.9 to 17.3 μM [ 35 ]. However, the fruit extract of G. xanthochymus in our study had no significant cytotoxic effect on five cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, the reported NMR data of GFC (Tables S1 and S2, ESI †) are not consistent with a type A structure according to our systematic study of structural confirmations of PPAPs. [24][25][26][27][28][29] Specifically, its C-1 chemical shift (d C 69.1) is much lower than that of type A PPAPs (about 80 ppm) but more consistent with that of type B structures (about 70 ppm). [29][30][31] Furthermore, almost all the reported PPAPs carrying a lavandulyl-derived substituent such as 2-isopropenyl-5-methyl-5-hexenyl (isolavandulyl) have type B structures, with this substituent located at the C-5 position, not the C-7 position as in GFC.…”
mentioning
confidence: 81%
“…[24][25][26][27][28][29] Specifically, its C-1 chemical shift (d C 69.1) is much lower than that of type A PPAPs (about 80 ppm) but more consistent with that of type B structures (about 70 ppm). [29][30][31] Furthermore, almost all the reported PPAPs carrying a lavandulyl-derived substituent such as 2-isopropenyl-5-methyl-5-hexenyl (isolavandulyl) have type B structures, with this substituent located at the C-5 position, not the C-7 position as in GFC. 23 If one swaps the 3,4-dihydroxybenzoyl and prenyl groups at C-1 and C-3 of GFC, and the isolavandulyl and prenyl groups at C-7 and C-5 of GFC, respectively, GFC is converted to xanthochymol (2), 32 a type B PPAP showing a very small difference with the wellknown compounds garcinol/guttiferone E (3/4) (Fig.…”
mentioning
confidence: 81%